2012
DOI: 10.1017/s1463423612000461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of welfare advice in primary care: effect on practice workload and prescribing for mental health

Abstract: Most GPs and CAB staff perceived the service reduced practice staff workload, although practice managers were less certain. CAB staff believed that many patients referred to them had mental health issues. Data were obtained for 148/250 referrals of whom 46% may have had a mental health issue. There were statistically significant reductions in the number of GP appointments and prescriptions for hypnotics/anxiolytics during the six months after referral to CABHO compared with six months before. There were also n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“… 36 Previous research using routinely collected medical record data found small reductions in GP consultation frequency and antidepressant prescription 6 months before and after receipt of co-located welfare advice. 37 However, this research was small and uncontrolled, precluding causal inference.…”
Section: Discussionmentioning
confidence: 98%
“… 36 Previous research using routinely collected medical record data found small reductions in GP consultation frequency and antidepressant prescription 6 months before and after receipt of co-located welfare advice. 37 However, this research was small and uncontrolled, precluding causal inference.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, our study adds important insights to the mixed evidence available on the effectiveness and e ciency of such schemes in reducing GP workload and healthcare demand more generally [14,15,35,36]. In particular, the non-signi cant ndings of many previous studies might be partially explained by the multicausal nature of their outcome indicators.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, our study adds important insights to the mixed evidence available on the effectiveness and e ciency of such schemes in reducing GP workload and healthcare demand more generally [16,17,37,38]. In particular, the non-signi cant ndings of many previous studies might be partially explained by the multicausal nature of their outcome indicators.…”
Section: Discussionmentioning
confidence: 74%